Application Of The Problem Based Instruction (PBI) Learning Model To Improve The Mathematical Problem Solving Abilities Of Students At SMP Negeri 12 Langsa - yarfan, medi; Zaki, Muhammad; Amalia, Rizki (Jurnal Dimensi Matematika, 2023)
Problem solving ability is a main goal in learning mathematics. Problem solving in mathematics learning must be developed, in the learning process students need to be accustomed to solving problems, both mathematical problems and everyday problems. In reality, students' mathematical problem-solving abilities are still relatively low, so a learning model is needed that can improve students' mathematical problem-solving abilities, namely the Problem Based Instruction learning model. The aim of the research is to determine the improvement in the mathematical problem-solving abilities of students at SMP Negeri 12 Langsa after experiencing mathematics learning by applying the Problem Based Instruction (PBI) learning model to spatial building material. This study uses a quantitative approach. The type of research used was pre-experimental design type one group pretest-posttest. The research population is all students in class VII of SMP Negeri 12 Langsa for the 2022/2023 academic year consisting of 2 classes with a total of 57 students. The sampling technique uses random sampling. The sample for this research was class VII-1 students with a total of 28 students. The research results obtained: dk=27 with a value of ttable = 2.052 and tcount = 56, the results obtained were tcount > ttable (14.55 > 2.052) with a significance level of 5% so H0 was rejected and Ha was accepted, it can be concluded that there was an increase in students' mathematical problem-solving abilities at SMP Negeri 12 Langsa after implementing the Problem Based Instruction (PBI) learning model.